469 FZD8 ACTIVATES THE BETA-CATENIN PATHWAY IN LUNG DEVELOPMENT. (1st January 2006) - Li, M.; Chen, H. Y.; Zhu, N. L.; Li, X.; Londhe, V.; Li, C. G.; Minoo, P.
Abstract : Purpose of Study: Frizzleds (Fzds) are a family of seven-transmembrane receptor proteins that mediate signaling of Wnts, the cystein-rich secreted molecules that play critical roles in various developmental processes. Strict regulation of spatial and temporal expression of Wnt and Fzd is critical for distinct functions of Wnts. In the current study, we have observed a cell-specific expression pattern of Fzd8 in lung and determined its function by overexpressing Fzd8 specifically in distal lung epithelia. Methods: Fzd8 distribution during lung morphogenesis was determined by IHC with Fzd8 antibody (R&D). We have generated and characterized transgenic mice with lung-specific overexpression of Fzd8 from the SpC promoter. To determine that transgenic Fzd8 is functional, Fzd8 transgenic mice were crossed with Top-gal transgenic mice, a reporter for canonical Wnt signaling. Lungs of the double transgenic mice were analyzed by β-Gal staining. Summary of Results: Fzd8 transgenic lines are postnatally viable. Fzd8 is highly expressed in proximal epithelial cells of developing lung after embryonic day 14 (E14). Overexpression of Fzd8 by Sp-C promoter results in proximalization of the distal epithelial airways around E15. Interestingly, this pattern of proximalization becomes normalized by E18. Lungs of double transgenic mice show increased β-Gal staining, suggesting that the Wnt/Beta-catenin pathway is activated by transgenic Fzd8. Conclusions: Our results show that Fzd8 activates the beta-catenin pathway in lung development. Supported by the Hastings Foundation, HL56590 & HL073471.